A tEEG framework for studying designer's cognitive and affective states. (17th November 2020) - Zhao, Mengting; Jia, Wenjun; Yang, Daocheng; Nguyen, Philon; Nguyen, Thanh An; Zeng, Yong
Abstract: This paper proposes a task-related electroencephalogram research framework (tEEG framework) to guide scholars' research on EEG-based cognitive and affective studies in the context of design. The proposed tEEG framework aims to investigate design activities with loosely controlled experiments and decompose a complex design process into multiple primitive cognitive activities, corresponding to which different research hypotheses on basic design activities can be effectively formulated and tested. Thereafter, existing EEG techniques and methods can be applied to analyse EEG signals related to design. Three application examples are presented at the end of this paper to demonstrate how the proposed framework can be applied to analyse design activities. The tEEG framework is presented to guide EEG-based cognitive and affective studies in the context of design. Existing methods and models are summarized, for the effective application of the tEEG framework, from the current literature spread in a wide spectrum of resources and fields.